Probiotics in Asthma and Allergy Prevention - Mennini, Maurizio; Dahdah, Lamia; Artesani, Maria Cristina; Fiocchi, Alessandro; Martelli, Alberto (Frontiers in Pediatrics, 2017)
Interest in probiotic research and its potential benefits in infant foods are relatively recent but significantly increasing. The evolution of the knowledge in the last twenty years made clear that alterations in the microbiome may be a consequence of events occurring during infancy or childhood, including prematurity, Caesarean section and nosocomial infections. Several evidences exist that a ‘healthy’ intestinal microbiota facilitates the development of immune tolerance. Interventional studies suggest that probiotics could be protective against the development of many diseases. Nevertheless, many factors complicate the analysis of dysbiosis in subjects with food allergy. Comparison in-between studies are difficult, because of considerable heterogeneity in study design, sample size and age at time faecal collection, methods of analysis of gut microbiome and geographic location. Currently there is no positive recommendation from scientific societies to use pre- or pro-biotics for treatment of food allergy or other allergic manifestations, while their use in prevention is being custom-cleared. However, the evidence basing the recommendations is still tiny. Although there is valid scientific evidence in vitro, there is not sufficient information to suggest the use of specific probiotics in allergy and asthma prevention.